A randomized clinical trial of granulocyte macrophage colony stimulating factor mouthwash for oral mucositis in head and neck cancer. (February 2022) - Dodd, Marylin J.; Cho, Maria H.; Cooper, Bruce A.; MacPhail, Laurie; Miaskowski, Christine
Abstract: Purpose: Oral mucositis (OM) is a significant problem for patients with head and neck cancer (HNC). The purpose of this double-blind, randomized clinical trial (RCT) was to evaluate the effectiveness of the granulocyte macrophage colony stimulating factor (GM-CSF) mouthwash compared to Salt and Soda mouthwash for both the prevention (prior to onset of OM) and treatment (beginning at the onset of OM to its healing) of radiation therapy (RT)-induced OM. Methods: A total of 91 patients with HNC were randomized to receive: GM-CSF throughout both the prevention and treatment phases (GG group); Salt and Soda throughout both phases (SS group) or Salt and Soda during the prevention phase followed by GM-CSF at the onset of OM (SG group). Three groups were compared on the occurrence and grades of OM, functional status, pain, chewing, and swallowing during and after RT. Results: No significant differences were found in the occurrence and grades of OM in the patients who used GM-CSF vs. Salt and Soda in the prevention phase. In addition, no differences were seen among the three groups in functional status, pain, chewing, and swallowing during and after RT. Conclusion: Given that GM-CSF was no more effective than Salt and Soda mouthwash for the prevention or treatment of OM, the readily available and cheaper mouthwash can be used at considerable cost savings. Highlights: Oral mucositis is significant clinical problem for patients with head and neck cancer. Oral mucositis results in pain and problems with nutritional intake. No differences were found in the onset of oral mucositis with the two mouthwashes.